A randomized placebo controlled trial of preoperative carbohydrate drinks and early postoperative nutritional supplement drinks in colorectal surgery. (24th June 2013) - Lidder, P.; Thomas, S.; Fleming, S.; Hosie, K.; Shaw, S.; Lewis, S.
Abstract Aim There is evidence that preoperative carbohydrate drinks and postoperative nutritional supplements improve the outcome of colorectal surgery. There is little information on their individual contribution. Method A prospective four‐arm double‐blind controlled trial was carried out in which patients were randomized to carbohydrate or placebo drinks preoperatively and a polymeric supplement or placebo drink postoperatively. The primary outcome was insulin resistance (using the short insulin tolerance test and HOMA‐IR). Secondary outcomes included handgrip strength, pulmonary function, intestinal permeability and postoperative complications. Results A total of 120 patients were randomized to four demographically well matched groups. Patients who received preoperative and postoperative supplements had better glucose homeostasis (P = 0.004), peak expiratory flow rate (P = 0.035), handgrip strength (P = 0.002) and less insulin resistance (P = 0.001) compared with those who only received placebo drinks. Conclusion Oral nutritional supplements given preoperatively and postoperatively improve postoperative handgrip strength, pulmonary function and insulin resistance. A weaker effect was seen in patients who received supplements either preoperatively or postoperatively. Oral nutritional supplements should be given both preoperatively and postoperatively.